Roux-en-Y gastric bypass-associated fecal tyramine promotes colon cancer risk via increased DNA damage, cell proliferation, and inflammation - Maria Glymenaki; Sophie Curio; Smeeta Shrestha; Qi Zhong; Laura Rushton; Rachael Barry; Mona El-Bahrawy; Julian R. Marchesi; Yulan Wang; Nigel J. Gooderham; Nadia Guerra; Jia V. Li (Microbiome)
Abstract Background Fecal abundances of Enterobacteriaceae and Enterococcaceae are elevated in patients following Roux-en-Y gastric bypass (RYGB) surgery. Concurrently, fecal concentrations of tyramine, derived from gut bacterial metabolism of tyrosine and/or food, increased post-RYGB. Furthermore, emerging evidence suggests that RYGB is associated with increased colorectal cancer (CRC) risk. However, the causal link between RYGB-associated microbial metabolites and CRC risk remains unclear. Hence, this study investigated the tyrosine metabolism of Enterobacteriaceae and Enterococcaceae strains isolated from patients post-RYGB and explored the causal effects of tyramine on the CRC risk and tumorigenesis using both human colonic cancer cell line (HCT 116) and wild-type and Apc Min/+ mice. Results We isolated 31 bacterial isolates belonging to Enterobacteriaceae and Enterococcaceae families from the feces of patients with RYGB surgery. By culturing the isolates in tyrosine-supplemented medium, we found that Citrobacter produced phenol as a main product of tyrosine, whereas Enterobacter and Klebsiella produced 4-hydroxyphenylacetate, Escherichia produced 4-hydroxyphenyllactate and 4-hydroxyphenylpyruvate, and Enterococcus and two Klebsiella isolates produced tyramine. These observations suggested the gut bacterial contribution to increased fecal concentrations of tyramine post-RYGB. We subsequently evaluated the impact of tyramine on CRC risk and development. Tyramine induced necrosis and promoted cell proliferation and DNA damage of HCT 116 cells. Daily oral administration of tyramine for 49 days to wild-type mice resulted in visible adenomas in 5 out of 12 mice, accompanied by significantly enhanced DNA damage (γH2AX +) and an increased trend of cell proliferation (Ki67 +) in the ileum, along with an upregulated expression of the cell division cycle gene (Cdc34b) in the colon. To evaluate the impact of tyramine on intestinal tumor growth, we treated Apc Min/+ mice with the same doses of tyramine and duration. These mice showed larger colonic tumor size and increased intestinal cell proliferation and inflammation (e.g., increased mRNA expression of IL-17A and higher number of Ly6G + neutrophils) compared to water-treated Apc Min/+ control mice. Conclusions Our results collectively suggested that RYGB-associated fecal bacteria could contribute to tyramine production and tyramine increased CRC risk by increasing DNA damage, cell proliferation, and pro-inflammatory responses of the gut. Monitoring and modulating tyramine concentrations in high-risk individuals could aid CRC prognosis and management. Video Abstract